Perkembangan islam di kalimantan - Asrofi, Nur-muchamad_ Muchamad (Maliki Interdisciplinary Journal, 2025)
This research aims to find out how the teachings of Islam entered and developed on the island of Kalimantan through trade, preaching, and friendship between previous kings. Kalimantan Island is the largest island in Indonesia which is famous as the “Island of a Thousand Rivers”. The process of Islamization in Kalimantan began in the 16th century, with the main influences coming from Gujarati traders, preachers from Java, and the influence of local kingdoms in Kalimantan. In South Kalimantan, the Sultanate of Banjarmasin became the center of the spread of Islam during the reign of Raden Samudera. In West Kalimantan, the spread of Islam was carried out by local kingdoms such as the Sambas Sultanate, the Matan Sultanate, and the Pontianak Sultanate who received Sufism teachings from Yemeni scholars, while in East Kalimantan, the Kutai Kartenegara Sultanate became the center of the spread of Islam through trade and preaching activities. The author hopes that this journal can be a reference for future writers in understanding the process of Islamization in Kalimantan Island.